(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2019)
يهدف هذا البحث إلى استخدام بعض طرائق التحليل الدالي، وتحديداً طرائق المؤثرات في فضاء هلبرت لتحويل مسالة القيمة الحديّة الابتدائية المتعلقة بالحركات الصغيرة لجملة هيدروديناميكية، (مجموعة من السوائل اللزجة + سائل مثالي) إلى مسألة كوشي بمعادلة تفاضلية من المرتبة الأولى في فضاء هلبرت , والبرهان على وجود حلّ قوي وحيد لهذه المعادلة. The aim of this paper is to use some concepts of functional analysis , especially the operator methods in Hilbert space to transform the initial boundary value problem concerning the small motions of a hydrodynamical system (system of viscous fluids + ideal fluid) to Cauchy problem for the differential operator equation of first order in the Hilbert space and to prove that there is a unique strong solution for this equation.